Photobiomodulation Attenuates Neurotoxic Polarization of Macrophages by Inhibiting the Notch1-HIF-1α/NF-κB Signalling Pathway in Mice With Spinal Cord Injury - Ma, Yangguang; Li, Penghui; Ju, Cheng; Zuo, Xiaoshuang; Li, Xin; Ding, Tan; Liang, Zhuowen; Zhang, Jiawei; Li, Kun; Wang, Xuankang; Zhu, Zhijie; Zhang, Zhihao; et al. (Frontiers in Immunology, 2022)
Spinal cord injury (SCI) is a catastrophic disease with a complex pathogenesis that includes inflammation, oxidative stress, and glial scar formation. Macrophages are the main mediators of the inflammatory response and are distributed in the epicentre of the SCI. Macrophages have neurotoxic and neuroprotective phenotypes (also known as classically and alternatively activated macrophages or M1 and M2 macrophages) that are associated with pro- or anti- inflammatory gene expression. Our previous study demonstrated that photobiomodulation (PBM) alters the polarization state of macrophages in the SCI region towards the M2 phenotype and promotes the recovery of motor function in rats with SCI. However, the mechanism by which PBM promotes SCI repair remains largely undefined. This study is based on the replacement of conventional percutaneous irradiation with implantable biofibre optic in vivo irradiation. The aim was to further investigate the effects of PBM on SCI in mice under new irradiation patterns and its potential mechanisms of action. PBM was administered to male mice with clamped SCI for four consecutive weeks and significantly promoted the recovery of motor function in mice. Analysis of the macrophage phenotypes in the epicentre of the SCI in mice showed that PBM mainly inhibited the neurotoxic activation of macrophages in the SCI area and reduced the secretion of inflammatory factors such as IL-1α and IL-6; PBM had no effect on M2 macrophages. Immediately afterwards, we constructed in vitro models of the inflammatory polarization of macrophages and PBM intervention. We found that PBM attenuated the neurotoxicity of M1 macrophages on VSC 4.1 motor neurons and dorsal root ganglion (DRG) neurons. The effects of PBM on neurotoxic macrophages and the possible mechanisms of action were analysed using RNA sequencing (RNA-seq), which confirmed that the main role of PBM was to modulate the inflammatory response and immune system processes. Analysis of the differentially expressed genes (DEGs) associated with the inflammatory response showed that PBM had the most significant regulatory effects on genes such as interleukin (IL)-1α, IL-6, cyclooxygenase-2 (COX-2), and inducible nitric oxide synthase (iNOS) and had obvious inhibitory effects on inflammation-related Notch1 and hypoxia-inducible factor-1α (HIF-1α) pathway genes. RNA-seq analysis of the effect of PBM on gene expression in resting-state macrophages and M2 macrophages did not show significant differences (data not shown). In conclusion, PBM promoted better motor recovery after SCI in mice by inhibiting the neurotoxic polarization of macrophages and the release of inflammatory mediators by acting on the Notch1-HIF-1α/NF-κB Signalling Pathway.